CELULOSE FIBROSA DO BAGACO DA CANA-DE-ACUCAR - AVALIACAO DA ACAO AGLUTINANTE/DESAGREGANTE EM COMPRIMIDOS CONTENDO FARMACO HIDROSSOLUVEL - Bueno, J. H F [UNESP]; Correa, Marcos Antonio [UNESP]; Oliveira, Anselmo Gomes de [UNESP]; Castro, Ana Doris de [UNESP]; Evangelista, Raul Cesar [UNESP] (My University, 1993)
In this work, a fibrous cellulose obtained from the sugar cane bagasse was analysed about its binder/disintegrating action and about its interference degree in the dissolution rate ('in vitro') of active principles, when incorporated in a compact system that has a water-soluble drug. It was used as reference drug the Lithium Carbonate, considering its solubility in water and it difficulties in the compressibility and flow rate. That cellulose was evaluated in a comparative study, involving another fibrous cellulose generally used in the tablet obtainment (Microcel 3E-200). After the experiment in methodologies of dry granulation and wet granulation, it was concluded that the analysed celluloses presents adequate binder/disintegrating efficience and they are equivalents in these aspect.
Fibrous cellulose of sugar cane bagasse - Valuation of the binder/disintegrating action in tablets that contain water-soluble drug
Keywords: binder/disintegrating excipient; fibrous cellulose; sugar cane cellulose; cellulose; lithium carbonate; magnesium stearate; talc; dissolution; drug formulation; drug granulation; drug solubility; tablet disintegration; tablet manufacture